A preliminary experiment regarding the natural induction of gonadal development in female Japanese eels without hormone treatment. (23rd September 2019) - Mikawa, Naomi; Yamada, Yoshiaki; Horie, Noriyuki; Okamura, Akihiro; Utoh, Tomoko; Tanaka, Satoru; Tsukamoto, Katsumi
Abstract: To test whether gonadal development of female eels could be promoted without any exogenous hormone treatments, we observed the effect of water temperature manipulation. After 3–5 months of water temperature treatments, three silver eels showed higher gonadosomatic indices (GSI). In particular, one eel in the 5–15°C fluctuating temperature treatment group (5°C daytime and 15°C night‐time) had the highest GSI of 8.5 with secondary yolk globule stage oocytes of large diameter (OD; 412 μm) after 3 months, which indicated definite gonadal development compared with those in the initial states (mean GSI, 2.4; OD, 226.7 μm). The 5–15°C fluctuating temperature and constant 5°C groups had low oocyte breakdown (atretic) rates. Because daily temperature fluctuations and cold daytime water are experienced by vertically migrating silver eels in the ocean, these temperature conditions may be key maturation process components that could be useful for hormone‐free artificial maturation.